The impact of service quality on behavioural intentions : the perspective of customers of private healthcare clinics in Sabah - Harry Ignatius Beatty (2004)
This research was conducted to study the influence of perceived service quality on behavioural intentions of customers of private healthcare clinics in Sabah, Malaysia. Zeithaml et aI.'s (1996) theoretical framework of behavioural intentions was used in the measurement of intentions, whereas the five dimensions of SERVQUAL (Parasuraman et al, 1988) was used in the measurement of perceived service quality. The results of the study provide strong support for empathy to predict customers' behavioural intentions and a weaker support for tangibles, reliability, and assurance to predict it. Contrary to studies made on the banking sector in Malaysia (Ndubisi, 2003a), the result was quite unexpected, which maybe due in part to the local setting and diverse cultures. Responsiveness had no influence on any of the behavioural intentions dimensions. The current research provides a strong support for the ability of perceived service quality (empathy) to predict behavioural intentions in the context of private healthcare clinics In Sabah, Malaysia. Theoretical and managerial implications of the findings are discussed.